2021
DOI: 10.1039/d1ra01095f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the number of nitrogen dopants on the electronic and magnetic properties of graphitic and pyridinic N-doped graphene – a density-functional study

Abstract: The number of dopant atoms is a parameter that can effectively tune the electronic and magnetic properties of graphitic and pyridinic N-doped graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…Figure a,d shows the same density of spin-up and spin-down states, indicating the nonmagnetic behavior of the graphitic-N1-doped single-layer and bilayer graphene. Compared with the pristine graphene layers with zero band gap, doping with graphitic-N causes the Fermi level to shift to the conduction band, resulting in energy gaps of 0.131 and 0.326 eV in graphitic N1-SLG and N1-BLG, respectively, which is consistent with previous theoretical studies. ,,, …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure a,d shows the same density of spin-up and spin-down states, indicating the nonmagnetic behavior of the graphitic-N1-doped single-layer and bilayer graphene. Compared with the pristine graphene layers with zero band gap, doping with graphitic-N causes the Fermi level to shift to the conduction band, resulting in energy gaps of 0.131 and 0.326 eV in graphitic N1-SLG and N1-BLG, respectively, which is consistent with previous theoretical studies. ,,, …”
Section: Resultssupporting
confidence: 90%
“…Compared with the pristine graphene layers with zero band gap, doping with graphitic-N causes the Fermi level to shift to the conduction band, resulting in energy gaps of 0.131 and 0.326 eV in graphitic N1-SLG and N1-BLG, respectively, which is consistent with previous theoretical studies. 69,70,74,76 A single vacancy generates a lack of electrons, creating an acceptor state in the valence band that pushes the Fermi level downward. The single vacancy obtained by the pyridinic defect configuration caused a shift of the Fermi levels into the valence band, turning the graphene structures into p-type semiconductors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, the optical and electronic properties of the CNP are mainly attributed to the C/N ratio. To simulate the lowest formation energy of those configurations, nitrogen atoms were incorporated in the CNP structure in pyridinic-N and graphitic-N. 36–38 The calculations showed that the bandgap of the CNP was reduced from 1.47 eV to 1.23 eV by increasing the nitrogen concentration from 5.6% to 9.9%, as can be seen in Fig. 4b .…”
Section: Resultsmentioning
confidence: 95%
“…[31] Graphitic N was found to provide a favorable ORR catalytic activity under neutral and alkaline conditions through a 2-electron transfer pathway. [31] These N species donate three electrons for the sp 2 configuration along with two electrons in the p z orbital, which can move to the stable π-conjugated system of graphite, leading to the positive charge of the graphitic N. [22,27,95,96] In addition to this, the sp 2 hybrid carbon skeleton possesses a π bond negative charge resulting from the additional lone pair electrons of the N atom, therefore enhancing the electron transport abilities and chemical reactivity of the material. [22,27,97] Pyrrolic N is also considered as one of the possible active sites due to its similar structure to pyrrolidine but fewer works are available on its role in ORR and OER.…”
Section: Nitrogen Atoms As Electrocatalytic Active Sitesmentioning
confidence: 99%